2003
DOI: 10.1128/aem.69.1.162-169.2003
|View full text |Cite
|
Sign up to set email alerts
|

Collagenolytic Serine-Carboxyl Proteinase fromAlicyclobacillus sendaiensisStrain NTAP-1: Purification, Characterization, Gene Cloning, and Heterologous Expression

Abstract: Enzymatic degradation of collagen produces peptides, the collagen peptides, which show a variety of bioactivities of industrial interest. Alicyclobacillus sendaiensis strain NTAP-1, a slightly thermophilic, acidophilic bacterium, extracellularly produces a novel thermostable collagenolytic activity, which exhibits its optimum at the acidic region (pH 3.9) and is potentially applicable to the efficient production of such peptides. Here, we describe the purification to homogeneity, characterization, gene cloning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 35 publications
(32 reference statements)
3
54
0
1
Order By: Relevance
“…Kumamolisin-As can cleave the -ProXaa*Yaa-sequence (here Xaa and Yaa denote the residues at the P 1 and P 1 ′ sites, respectively). One experimental observation that is of considerable interest is the fact that this enzyme generally has higher specificity for the substrates with a positively charged residue at the P 1 site than for those they do not carry such charge (3,9). For instance, it was found that the k cat value for a substrate containing the -ProArg*Gly sequence is ∼65-fold higher than for a substrate containing the -Pro-Gly*Gly sequence and the K M is ∼6.5-fold higher, leading to 10-fold increase of k cat /K M (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kumamolisin-As can cleave the -ProXaa*Yaa-sequence (here Xaa and Yaa denote the residues at the P 1 and P 1 ′ sites, respectively). One experimental observation that is of considerable interest is the fact that this enzyme generally has higher specificity for the substrates with a positively charged residue at the P 1 site than for those they do not carry such charge (3,9). For instance, it was found that the k cat value for a substrate containing the -ProArg*Gly sequence is ∼65-fold higher than for a substrate containing the -Pro-Gly*Gly sequence and the K M is ∼6.5-fold higher, leading to 10-fold increase of k cat /K M (3).…”
mentioning
confidence: 99%
“…Kumamolsin-As belongs to the recently characterized family of serine-carboxyl peptidases (sedolisins) that were originally described by Murao, Oda, and co-workers about 20 years ago (1)(2)(3). Sedolisins are present in a wide variety of organisms, including archaea, bacteria, molds, slime molds (mixomycetes), amoebas, fishes, and mammals, and they are active at low pH and often high temperature.…”
mentioning
confidence: 99%
“…Although initially reported as being collagenolytic, the Ser proteases fibroblast activation protein/separase and trypsin-2 do not cleave interstitial collagens within their triple helices (20). 3 Additional interstitial collagenases include several that act under acidic conditions, such as Cynara cardunculus Asp protease cardosin A (22) and Alicyclobacillus sendaiensis Ser-carboxyl protease kumamolisin-As/ScpA (23), as well as the Cys proteases ginger (Zingiber officinale) GP2 and GP3 (24) and Fasciola hepatica FhCL2 and FhCL3 (25). GP2 hydrolyzes type I collagen at three distinct sites (Table 1) (24).…”
mentioning
confidence: 99%
“…The result of the present study was close to that obtained by Lima et al, 35 in the production of collagenase enzyme by Candida albicans, which had a value of 7.06 U mL -1 . Nakayama et al, 36 studied the production of collagenase enzyme by Bacillus NATP-1, previously described as A. sendaiensis, 4 and obtained enzymatic activity of 24 U mL -1 through the use of oxygen and pH control during enzyme production in a potato dextrose broth medium. These same authors also evaluated enzyme production in the presence of collagen and gelatin to 1.5% (w/v), and found that this factor did not induce collagenase production.…”
Section: Production Of Collagenase By Alicyclobacillus Sendaiensis Kcmentioning
confidence: 99%
“…1 Enzymes produced by such microorganisms have been studied for use in various industrial applications, including galactosidase, esterases, proteases and amylases, due to their thermostable characteristics. [2][3][4][5] The Alicyclobacillus acidocaldarius and Alicyclobacillus sendaiensis species have been evaluated for the production of both amylase and collagenase, respectively.…”
Section: Introductionmentioning
confidence: 99%